Advances in formal Slavic linguistics 2017 - Marušič, Franc; Žaucer, Rok; Mišmaš, Petra (Language Science Press, 2020)
Advances in Formal Slavic Linguistics 2017 is a collection of fifteen articles that were prepared on the basis of talks given at the conference Formal Description of Slavic Languages 12.5, which was held on December 7-9, 2017, at the University of Nova Gorica. The volume covers a wide array of topics, such as control verbs, instrumental arguments, and perduratives in Russian, comparatives, negation, n-words, negative polarity items, and complementizer ellipsis in Czech, impersonal se-constructions and complementizer doubling in Slovenian, prosody and the morphology of multi-purpose suffixes in Serbo-Croatian, and indefinite numerals and the binding properties of dative arguments in Polish. Importantly, by exploring these phenomena in individual Slavic languages, the collection of articles in this volume makes a significant contribution to both Slavic linguistics and to linguistics in general.